Social employee well-being challenges of academics in the hybrid work environment - Rudo Rachel Marozva; Anna-Marie Pelser (Frontiers in Psychology)
The complex nature of the hybrid work environment impacts on the overall well-being of employees. There is limited research on how the hybrid work environment has impacted the social dimension of employee well-being, particularly among academics in higher education institutions. The aim of the study was to explore and understand social well-being challenges that academics face as a result of the hybrid work environment. The study adopted a cross-sectional qualitative research approach and used semi-structured interviews using an interview guide to collect data. The sample included 23 academics who are representatives of the three campuses of North-West University. Thematic analysis was used to analyse the data. Three themes emerged from the analyses of data: social connections, sense of belonging and work relationships. The social connections theme had four sub-themes: social isolation, informal communication breakdown, limited networking and personality conflict. Sense of belonging theme entailed four sub-themes: lack of resources, work-life imbalance, onboarding challenges and non-inclusive work environment. Relationships theme had three sub-themes: lack of trust, reduced social support and delayed feedback. Experiences of the research participants are noted to comprehend the negative impact of the hybrid work environment on social employee well-being. The findings suggest that social well-being challenges that academics face are heightened by the nature of the industry, personality traits and the context of the study which is Africa. This requires HEIs to explore the internal and external environment when managing social well-being challenges that academics face as a result of the hybrid work environment.